Review of Dam Effects on Native and Invasive Crayfishes Illustrates Complex Choices for Conservation Planning - Barnett, Zanethia C.; Adams, Susan B. (Frontiers in Ecology and Evolution, 2021)
Dams are among the most prevalent and extreme alterations humans have perpetrated on fluvial systems. The dramatic physical and biological changes caused by dams have been synthesized for many aquatic faunal groups, but not for crayfishes. In addition, invasive crayfish species are an increasing threat to global biodiversity, and dams have both costs and benefits with respect to crayfish invasions. North American crayfishes have imperiled native crayfishes in Europe, largely by hosting and spreading the crayfish plague pathogen Aphanomyces astaci that is lethal to European crayfishes. The differential effects of A. astaci on North American versus European crayfishes contribute to differences between the continents in the costs and benefits of dams. We reviewed literature on both the detrimental and beneficial effects of dams on crayfishes, with emphasis on conservation of European crayfishes. We also suggested additional potential dam effects that warrant investigation. Our review illustrates the challenges and opportunities dams create for crayfish conservation. Dams create detrimental effects to native crayfishes, including reducing suitable habitats necessary for native habitat-specialist species and creating habitats suitable for non-native habitat-generalist species; fragmenting crayfish populations; and reducing species’ ability to recolonize upstream habitats. Conversely, dams can have beneficial effects by creating barriers that slow or halt upstream invasions by non-native crayfishes and spread of the crayfish plague. The complexity of the issues and the limited ecological information available highlights the need for future studies on the effects of dams on crayfishes. Crayfishes are one of the most imperiled groups of aquatic fauna globally, therefore, understanding the beneficial and detrimental effects of dams is essential for effective conservation of many crayfish species.